Design of Porous Microparticles Based on Chitosan and Methacrylic Monomers. Issue 32 (26th August 2019) - Vasiliu, Silvia; Lungan, Maria‐Andreea; Gugoasa, Ionela; Drobota, Mioara; Popa, Marcel; Mihai, Marcela; Racovita, Stefania
Abstract: Starting from glycidyl methacrylate, three dimethacrylic monomers (mono, di and triethylene glycol dimethacrylate) and chitosan, various types of porous microparticles were obtained by suspension polymerization technique. Also, using the same technique the un‐grafted porous microparticles were obtained by reaction between glycidyl methacrylate and dimethacrylic monomers. The successful grafting reaction of chitosan onto synthetic polymer networks was highlighted by FTIR spectroscopy, scanning electron microscopy, atomic force microscopy and thermogravimetric analysis. The dimensional analysis of all type of microparticles was performed by laser diffraction while the specific surface areas were determined by means of dynamic vapor sorption. Grafting of polysaccharide onto crosslinked networks has led to the preparation of polymeric materials with high specific surface area (50‐160 m 2 /g) and better swelling capacities (101‐106%) compared to microparticles based on glycidyl methacrylate and dimethacrylic monomers [(31‐69 m 2 /g) and (39‐57%), respectively]. Furthermore, the sorption properties of grafted and un‐grafted microparticles were tested using Cu(II) solution. The highest retention capacity value of Cu(II) (41.7 mg/g) was obtained when the C1 microparticles were used in the adsorption studies. Abstract : Grafting of chitosan onto crosslinked networks based on glycidyl methacrylate has led to the preparation of the polymeric materials with high specific surface area and better swelling capacities compared to the un‐grafted microparticles. The grafted microparticles can be good candidates as sustained drug delivery systems or as adsorbents for Wilson disease treatment as well as in waste water purification.